Answer:
6x-11y=-13
Step-by-step explanation:
(x1,y1)=(3/2,2) and (x2,y2)=(-4,-1)
y-y1= y2-y1/x2-x1 (x-x1)
y-2=-3/-11/2(x-3/2)
=6/11(x-3/2)
11(y-2)=6x-9
11y-22=6x-9
6x-11y=9-22
6x-11y=-13
3) 0.825
4) 0.1212
5) 0.5455
6) -7.177
7a) 0.066
b) 0.166
c) 0.333
d) 0.416
8) -2/5
9) -7 (32/100) = -7 (9/25)
10) 0.22222 = 2/9
Hello!
A function is that y only has 1 solution for every x
-3x + 8 = y is a function because it only has one y value for every x
y = x^2 + 3 is a function because it has only one y value for every x
y^2 = x is not a function because it has two y values for x = 4
Hope this helps!